Glycogen Synthase Kinase 3β and Activin/Nodal Inhibition in Human Embryonic Stem Cells Induces a Pre‐Neuroepithelial State That Is Required for Specification to a Floor Plate Cell Lineage123. (22nd October 2012) - Denham, Mark; Bye, Chris; Leung, Jessie; Conley, Brock J.; Thompson, Lachlan H.; Dottori, Mirella
Abstract: The floor plate is one of the major organizers of the developing nervous system through its secretion of sonic hedgehog (Shh). Although the floor plate is located within the neural tube, the derivation of the floor plate during development is still debatable and some studies suggest that floor plate cells are specified by Shh in a temporarily restricted window different to neuroepithelial cells. Using human embryonic stem cells (hESC) as a model of neurogenesis, we sought to determine how floor plate cells may be temporarily specified by SHH signaling during human embryogenesis. We found that inhibition of both GSK3β and activin/nodal pathways in hESC induces a cellular state of SOX2+/PAX6− expression, we describe as "pre‐neuroepithelial." Exposure of SHH during this pre‐neuroepithelial period causes the expression of GLI transcription factors to function as activators and consequently upregulate expression of the floor plate marker, FOXA2, while also supressing PAX6 expression to inhibit neuroepithelial fate. FOXA2+ cells were able to efficiently generate mesencephalic dopaminergic neurons, a floor plate derivative. Overall, this study demonstrates a highly efficient system for generating floor plate cells from hESC and, most importantly, reveals that specification of floor plate cells is temporally dependent, whereby it occurs prior to the onset of PAX6 expression, within a pre‐neuroepithelial stage. STEM CELLS 2012;30:2400–2411